Loss-of-function mutations inSCN4Acause severe foetal hypokinesia or ‘classical’ congenital myopathy - Irina Zaharieva; Michael G. Thor; Emily C. Oates; Clara van Karnebeek; Glenda Hendson; Eveline W Blom; Nanna Witting; Magnhild Rasmussen; Michael T. Gabbett; Gianina Ravenscroft; Maria Sframeli; Karen Suetterlin; et al. (2015)
Congenital myopathies are a clinically and genetically heterogeneous group of muscle disorders characterized by congenital or early-onset hypotonia and muscle weakness, and specific pathological features on muscle biopsy. The phenotype ranges from foetal akinesia resulting in in utero or neonatal mortality, to milder disorders that are not life-limiting. Over the past decade, more than 20 new congenital myopathy genes have been identified. Most encode proteins involved in muscle contraction; however, mutations in ion channel-encoding genes are increasingly being recognized as a cause of this group of disorders. SCN4A encodes the α-subunit of the skeletal muscle voltage-gated sodium channel (Nav1.4). This channel is essential for the generation and propagation of the muscle action potential crucial to muscle contraction. Dominant SCN4A gain-of-function mutations are a well-established cause of myotonia and periodic paralysis. Using whole exome sequencing, we identified homozygous or compound heterozygous SCN4A mutations in a cohort of 11 individuals from six unrelated kindreds with congenital myopathy. Affected members developed in utero- or neonatal-onset muscle weakness of variable severity. In seven cases, severe muscle weakness resulted in death during the third trimester or shortly after birth. The remaining four cases had marked congenital or neonatal-onset hypotonia and weakness associated with mild-to-moderate facial and neck weakness, significant neonatal-onset respiratory and swallowing difficulties and childhood-onset spinal deformities. All four surviving cohort members experienced clinical improvement in the first decade of life. Muscle biopsies showed myopathic features including fibre size variability, presence of fibrofatty tissue of varying severity, without specific structural abnormalities. Electrophysiology suggested a myopathic process, without myotonia. In vitro functional assessment in HEK293 cells of the impact of the identified SCN4A mutations showed loss-of-function of the mutant Nav1.4 channels. All, apart from one, of the mutations either caused fully non-functional channels, or resulted in a reduced channel activity. Each of the affected cases carried at least one full loss-of-function mutation. In five out of six families, a second loss-of-function mutation was present on the trans allele. These functional results provide convincing evidence for the pathogenicity of the identified mutations and suggest that different degrees of loss-of-function in mutant Nav1.4 channels are associated with attenuation of the skeletal muscle action potential amplitude to a level insufficient to support normal muscle function. The results demonstrate that recessive loss-of-function SCN4A mutations should be considered in patients with a congenital myopathy.